Investigation Action Against Children Who Are Circulating Pharmaceuticals Stocks That Does Not Have Permission In Jurisdictions Police Resort (Polres) Kudus - Indra Narotama; Lathifah Hanim (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2019)
This research to know the legal basis for investigation of cases of children who distribute pharmaceutical preparation which does not have a marketing authorization, the implementation of the investigation on the case of children who distribute pharmaceutical preparation which does not have a marketing authorization in the territory of the police station of the Kudus, barriers and solutions in the implementation of the investigation on the case of children who circulate preparations pharmacy that does not have a marketing authorization in the territory of the Kudus Police.The method used is empirical juridical methods. Specifications research used the descriptive analysis. Data was collected by interviewing the parties involved in research, direct observation and recording of documents.The results showed that the basic legal basis for investigation of trafficking cases and abuse of pharmaceutical preparations without a marketing authorization is Act No.36 of 2009 on Health, which sentencing criminal offense trafficking and abuse of pharmaceutical preparations without a marketing authorization provided for in Article 197, it refers to the the provisions of Article 106 paragraph (1) in the form of pharmaceutical preparations and medical devices can only be released after obtaining marketing authorization. The process of investigation of the case of children who distribute pharmaceuticals do not have a marketing authorization in the territory of the Kudus Police have been done by the procedural law in Indonesia, namely the Criminal Code, it is proved to have been implemented procedures Investigators action in the process of investigation. The process of investigation is also under the provisions of Article 189Undang Act No. 36 of 2009 on Health and Act No. 3 of 1997 on Juvenile Court and the provisions of Article 82 of Act No. 23 of 2002 on Child Protection. Barriers faced by investigators Kudus Police in carrying out investigation on the case of children who distribute pharmaceuticals do not have a marketing authorization in the jurisdiction of the Kudus Police is limited both the quantity and quality of human resources of law enforcement officers who understand the case for children, operating costs, low awareness of the witness in attending the examination process, the lack of legal awareness of the society and time specified in the investigation of cases children are very little, while filing must be submitted as soon as possible.Keywords: Investigation; Children; Pharmacy Circulation Without Permission.